Developmental changes of opsin gene expression in ray-finned fishes (Actinopterygii) - Lupše, Nik; Kłodawska, Monika; Truhlářová, Veronika; Košátko, Prokop; Kašpar, Vojtěch; Bitja Nyom, Arnold Roger; Musilova, Zuzana (Proceedings. Biological sciences, 2022)
Fish often change their habitat and trophic preferences during development. Dramatic functional differences between embryos, larvae, juveniles and adults also concern sensory systems, including vision. Here, we focus on the photoreceptors (rod and cone cells) in the retina and their gene expression profiles during development. Using comparative transcriptomics on 63 species, belonging to 23 actinopterygian orders, we report general developmental patterns of opsin expression, mostly suggesting an increased importance of the rod opsin (RH1) gene and the long-wavelength-sensitive cone opsin, and a decreasing importance of the shorter wavelength-sensitive cone opsin throughout development. Furthermore, we investigate in detail ontogenetic changes in 14 selected species (from Polypteriformes, Acipenseriformes, Cypriniformes, Aulopiformes and Cichliformes), and we report examples of expanded cone opsin repertoires, cone opsin switches (mostly within RH2) and increasing rod : cone ratio as evidenced by the opsin and phototransduction cascade genes. Our findings provide molecular support for developmental stage-specific visual palettes of ray-finned fishes and shifts between, which most likely arose in response to ecological, behavioural and physiological factors.
Keywords: tyčinkové opsiny; exprese genu; Rod Opsins; Gene Expression; gene expression; ryby; opsin; Opsins; development; vision; zvířata; Retinal Cone Photoreceptor Cells; Fishes; Cone Opsins; čípky retiny - opsiny; opsiny; Actinopterygii; Animals; evolution; čípky retiny